Type and Typography / International Typographic Association - International Typographic Association (2009)
[Dt.:] Datenbank mit Videos zu verschiedenen Themen der Typografie; dazu Informationen über den Verband, Konferenzen sowie den ATypI-Preis "Prix Charles Peignot for Excellence in Type Design"; Archiv ab 1997 - [Engl.:] Database with videos on various typographical subjects; also information about the association, conferences as well as the ATypI prize "Prix Charles Peignot for Excellence in Type Design"; archive beginning in 1997.